Application of Organic and Inorganic Fertilizer to Percentage of Attacks of Ganjur Pest (Orseolia oryzae) in Rice - Benauli, Arkhiadi; Sitohang, Nurdin; Gusriani, Yunda; Hutasoit, Jaya Febrianto (Agrosains : Jurnal Penelitian Agronomi, 2023)
Rice plants are a staple food for Indonesian people. Low crop productivity causes farmers to feel at a loss. Low rice yields are also caused by pests that attack plants, one of which is ganjur (Orselia oryzae). Efforts must be made to suppress the ganjur attack by trialling fertilizer application to rice plants. Research was conducted to determine the effect of fertilizer application in reducing the percentage of Orseolia oryzae attacks on rice plants. The method used in this research used a randomized block design (RBD) with 1 treatment factor, namely the type of fertilizer. The treatment levels for the types of fertilizer used are as follows: F0: control; F1: Cow dung; F2: Composted Organic Fertilizer; F3: Single NPK Fertilizer, P4: Compound NPK Fertilizer (16:16:16). The research began with making organic fertilizer (cow dung and compost), planting, applying treatment, collecting data, and analyzing observation data. The research results show that the application of cow dung fertilizer provides the best results compared to other fertilizers. The application of cow dung fertilizer produced the highest data based on the observed variables in this study, namely number of tillers, number of panicles, weight of 1000 grains, production per plot and reduced percentage of gallbladder pest attacks. Based on this research, the application of cow dung fertilizer can suppress attacks by ganjur pests (Orselia oryzae) while increasing the productivity of rice plants.